2021
DOI: 10.3399/bjgp.2020.0856
|View full text |Cite
|
Sign up to set email alerts
|

Experience of implementing and delivering group consultations in UK general practice: a qualitative study

Abstract: Background: Group consultations are a relatively new concept in UK primary care and are a suggested solution to current workload pressures in general practice. However, little is known about the experience of implementing and delivering this approach from staff and organisational perspectives. Aim: To explore the experience of implementing and delivering group consultations in general practice. Design: Qualitative telephone interview study. Methods: Topic guides explored the perspectives and experiences of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…Challenges to implementation of SMAs reported by providers and SMA trainers in this study echo the ndings of Swaithes et al (7), which reported key challenges to the initiation and operationalisation of group consultation in primary care related to the amount of time and resource required to set-up the SMAs in practice. We also found that practice-wide 'buyin' was needed to successfully adopt and support this model, and that staff understanding and attitudes underpinned success.…”
Section: Comparison With Existing Literaturesupporting
confidence: 79%
See 2 more Smart Citations
“…Challenges to implementation of SMAs reported by providers and SMA trainers in this study echo the ndings of Swaithes et al (7), which reported key challenges to the initiation and operationalisation of group consultation in primary care related to the amount of time and resource required to set-up the SMAs in practice. We also found that practice-wide 'buyin' was needed to successfully adopt and support this model, and that staff understanding and attitudes underpinned success.…”
Section: Comparison With Existing Literaturesupporting
confidence: 79%
“…Whilst it has been reported that over 100 practices across England have attended SMA training (3), the extent to which practices have successfully used the model is unclear. A review of the wider literature identi ed several barriers to implementation including administrative and resource challenges, patient resistance and suitability and role adjustments and uncertainties (7). Factors identi ed as supporting successful implementation in primary care include having leadership, teamwork and communication, alongside staff skilled in group facilitation (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also growing recognition amongst practitioners that supporting individuals to self‐care also has benefits for healthcare staff. For example, clinicians involved in delivering group consultations report developing better relationships with patients and colleagues 23 and feel more satisfied with their work 24 . This may in turn reduce healthcare professional's risk of burnout whilst improving their experience and the quality of their interaction with patients.…”
Section: How Does the Future Need To Be Different?mentioning
confidence: 99%
“…Before the pandemic, group consultations (or shared medical appointments) started to gain traction as a potential means for managing rising demand in general practice. 2 , 8 12 Combining clinical care with elements of group education and peer support, group consultations have been delivered in a variety of formats for patients with long-term conditions or shared health concerns. 8 , 13 …”
Section: Introductionmentioning
confidence: 99%